2021
DOI: 10.15252/emmm.202113933
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasites differentially sense environmental elasticity during transmission

Abstract: Transmission of malaria‐causing parasites to and by the mosquito relies on active parasite migration and constitutes bottlenecks in the Plasmodium life cycle. Parasite adaption to the biochemically and physically different environments must hence be a key evolutionary driver for transmission efficiency. To probe how subtle but physiologically relevant changes in environmental elasticity impact parasite migration, we introduce 2D and 3D polyacrylamide gels to study ookinetes, the parasite forms emigrating from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…1 and Movies S1 and S2 ). The average P. falciparum merozoite gliding speed was 0.6 μm/s (SD = 0.14 μm/s; n = 10 individual merozoites), considerably slower than that of P. yoelii sporozoites (helical gliding 5.0μm/s; SD = 0.83 μm/s; n = 8) and P. berghei sporozoites (2 μm/s to 3 μm/s) ( 18 ), Toxoplasma gondii tachyzoites (helical gliding 2.6 μm/s; SD = 0.54 μm/s; n = 13; circular gliding 1.8 μm/s; SD = 0.32 μm/s; n = 13), and Babesia bovis merozoites (6.0 μm/s; SD = 0.73 μm/s; n = 5), but significantly faster than P. berghei ookinetes (helical gliding 5.8 μm/min) ( 19 ). The longest gliding time of P. falciparum merozoites was 43 s, shorter than those of P. yoelii sporozoites (>600 s), T. gondii tachyzoites (>600 s), and B. bovis merozoites (125 s).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…1 and Movies S1 and S2 ). The average P. falciparum merozoite gliding speed was 0.6 μm/s (SD = 0.14 μm/s; n = 10 individual merozoites), considerably slower than that of P. yoelii sporozoites (helical gliding 5.0μm/s; SD = 0.83 μm/s; n = 8) and P. berghei sporozoites (2 μm/s to 3 μm/s) ( 18 ), Toxoplasma gondii tachyzoites (helical gliding 2.6 μm/s; SD = 0.54 μm/s; n = 13; circular gliding 1.8 μm/s; SD = 0.32 μm/s; n = 13), and Babesia bovis merozoites (6.0 μm/s; SD = 0.73 μm/s; n = 5), but significantly faster than P. berghei ookinetes (helical gliding 5.8 μm/min) ( 19 ). The longest gliding time of P. falciparum merozoites was 43 s, shorter than those of P. yoelii sporozoites (>600 s), T. gondii tachyzoites (>600 s), and B. bovis merozoites (125 s).…”
Section: Resultsmentioning
confidence: 89%
“…Thus, while these results do not rule out the possibility of gliding within tissue compartments, they do suggest that gliding is unlikely to support extravasation of free merozoites and that merozoite motility may be specific to erythrocyte lineages and highly adherent artificial surfaces. While sporozoites are known to glide readily in both mosquito and human tissue environments, they have recently been shown to not glide on HUVECs ( 18 )—suggesting that specific cell types may be nonpermissive for motility even for zoites with relatively broad gliding substrate specificities.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that rounded sporozoites could not efficiently enter into and pass through the salivary canals. To test if sporozoites fail to migrate through confined spaces, we squeezed a salivary gland between a glass slide and a polyacrylamide gel such that sporozoites were liberated and able to enter into the gel (Figure 6F) (Ripp et al, 2021). On the surface of the gel both deformed and normally shaped parasites are readily visible, while at the bottom end of the gel, only normally shaped sporozoites were found (Figure 6F-G), indicating that deformed sporozoites could not cross the dense matrix of the gel.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of infectivity of trep(-)/tlp(-) sporozoites transmitted by mosquito bite is likely a result of the decreased numbers in salivary glands as for trep(-) parasites [ 60 ]. In addition there might be an effect of slower migration in the skin, but this would need further experiments using sensitive in vitro assays such as our recently established 3D gel-based assay [ 27 ] or in vivo imaging, which would require fluorescent parasite lines and much time. Both experiments are nearly impossible to achieve in parasite lines with strongly reduced salivary gland loads.…”
Section: Discussionmentioning
confidence: 99%
“…Sporozoites migrate through cells in the dermis, a capacity that is essential for entering the circulatory system [ 24 , 25 ]. Sporozoites can enter both blood or lymph vessels [ 18 ] and those entering the blood are transported throughout the body to reach the liver [ 26 , 27 ]. In the liver sporozoites enter and differentiate within hepatocytes into red cell infecting merozoites [ 25 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%